Preservice Teachers’ Perception on the Implementation of Online Project-Based Learning - Ringotama, Arrizalu Arsa; Setyaningsih, Endang; Handayani, Ellisa Indriyani Putri (JOLLT Journal of Languages and Language Teaching, 2022)
Current studies provide compelling evidence that project-based learning (PBL) is an effective method for the students. Considering the empirical findings, PBL is highly endorsed in many EFL contexts. However, with the major shift to online learning due the pandemic, little is known about the possibility of PBL implementation within this new context. This current case study attempts to portray the PBL implementation within the online context and how the students perceive the implementation. The study was carried out in an English Education Department involving 36 seventh-grade preservice teachers (PTs). The data were collected through classroom observations, online questionnaires, and in-depth semi-structured interviews. The data were analyzed using the interactive model and the results of the analysis show the stages of PBL can be implemented in the similar way to that in the offline setting. However, the technological use in the online setting differs in terms of the amount of its usage frequency. The study also revealed that the students consider the implementation of PBL in online setting as challenging yet motivating. The findings imply that the changes of teaching and learning setting do not affect the durability of the PBL. It means that with a little tweak, mainly in terms of technological usage, grouping and group communication, PBL might be successfully implemented in the online setting.